Answer:
(-7,-15)
Explanation:
We can substitute first y in the second y. Both equations are also functions. We can merge the equations.
![2x - 1 = x - 8 \\ 2x - x = - 8 + 1 \\ x = - 7](https://img.qammunity.org/2022/formulas/mathematics/middle-school/f54e5ttruz0jwrasdmzq1ra7bz0d4gma1n.png)
Substitute x = -7 in any given equations. I will choose the second equation to substitute in.
![y = x - 8 \\ y = - 7 - 8 \\ y = - 15](https://img.qammunity.org/2022/formulas/mathematics/middle-school/msk1t1e1yyccl0dl9gznf6iwg2ofb1f0j3.png)
Answer Check
Substitute both x and y in both equations.
![- 15 = 2( - 7) - 1 \\ - 15 = - 14 - 1 \\ - 15 = - 15](https://img.qammunity.org/2022/formulas/mathematics/middle-school/iee8phcohdswf7p2zrd041kwwxq2fq7l9e.png)
The equation is true for (-7,-15).
![- 15 = - 7 - 8 \\ - 15 = - 15](https://img.qammunity.org/2022/formulas/mathematics/middle-school/5eb4dacwk2qethm5rlv3cvvfck8ull0899.png)
The second equation is true for (-7,-15).
Therefore our answer is (-7,-15)